Fluid evolution and paleo-pressure recovery by Raman quantitative analysis in the Shahejie Formation of the western slope belt in Dongpu Sag, Bohai Bay Basin, China - Tang, Youjun; Wu, Yijun; Wang, Ruyue; Huang, Yahao; Xue, Yifan; Chen, Zhonghong; Xu, Tianwu; Wang, Ting; Li, Hongbo (Frontiers in Earth Science, 2023)
Inorganic and organic fluids are widely found in sedimentary basins during oil and gas migration and accumulation. This research investigates two types of sandstone reservoirs with different pressure states and fluid evolution of the Shahejie Formation in the western slope belt of Dongpu Sag. Based on petrographic observations, micro-Raman spectroscopy, and fluorescent spectrometry, petroleum inclusions, CH4-bearing inclusions, and CO2-bearing inclusions were discovered in quartz-hosted minerals. The pressure–temperature–time–composition (P–T–t–X) properties of the CH4 and CO2 inclusions were obtained by quantitative Raman analysis and thermodynamic models. Minimum trapped pressure was predicted by the thermodynamic modeling of petroleum inclusions. Saffron yellow petroleum inclusions represent an early Oligocene oil-charging event (∼32–30 Ma), and the two kinds of reservoirs were all kept in moderate-overpressure conditions (average pressure coefficient: 1.26). Due to rapid uplift and denudation (Dongying movement) in the middle Oligocene in step II, crude oil degrades into CH4 and CO2 (density of CH4 gas inclusions: 0.1010–0.1339 g/cm3; density of CO2 gas inclusions: 0.450–0.612 g/cm3) and retains low-maturity (0.67–1.04%) bitumen in situ. Tectonic destruction causes the reservoir to be released to normal pressure. With the reburial of the Es3 Formation, step II entered the middle stage of oil generation again (average pressure coefficient: 0.90). However, in step I, with secondary hydrocarbons occurring, second-stage oil (performance for pale blue fluorescence in petroleum inclusions) accumulated at ∼12–0 Ma (late Miocene–Pliocene). The second oil charging event in step I remains a reservoir under high-overpressure conditions (average pressure coefficient: 1.67).